Contractual Interpretation - Winkelmann, Helen; Glazebrook, Susan; France, Ellen (Victoria University of Wellington Law Review, 2020)
This article starts with some general points about the interpretation of contracts, before discussing in more detail the methodology of interpretation and, in particular, the modern purposive approach to interpretation with its greater use of extrinsic aids to interpretation.